KEMAMPUAN RASIO KEUANGAN DALAM MEMPREDIKSI RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2018 - Alfiyanita Alfiyanita (JURNAL PUNDI, 2020)
Fast traslate Icon translate The purpose of this study conducted to enhance the knowledge about of profitability and Solvability on stock returns. The population is all companies which are listed in Indonesia Stock Exchange in 2014-2018 periods. The sample collection technique has been carried out by using purposive sampling method with 83 companies have been selected as samples. The analytical method used is regression analysis of panel data with the help of application E-Views 8. The study show that profitability have positive and significant influence on Stock Return in Indonesia, and Solvability have positive and significant influence on Stock Return.